Perseverance Strategies for Enterprising Individuals - Van Gelderen, Marco (My University)
Purpose: To arrive at a conceptual understanding of perseverance processes in the context of enterprising behavior. To outline readily employable perseverance strategies for situations characterized by obstacles, challenges and setbacks. Approach: This paper presents a process model of perseverance, drawing on elements of control theory (Carver and Scheier 1981, 1998) and appraisal theory (Lazarus, 1966, 1999; Lazarus and Folkman, 1984). Findings: From this model, it derives a variety of perseverance strategies within four broad categories: strategies that affect adversity itself; strategies that change the way adversity is perceived; strategies that reframe the aim that adversity has made difficult to attain; and strategies that help to increase self-regulatory strength. James Dyson‟s biography provides examples for the strategies. Research implications: A research agenda is provided. Practical implications: A broad variety of strategies are discussed help individuals to persevere in reaching their enterprising goals. Social implications: This paper aims to contribute to the persevering abilities of enterprising individuals. Originality/Value: Although it is a widely held perception that perseverance is needed to successfully start and run a venture, the perseverance process and perseverance strategies have received little research attention. Classification of Paper type: Post-print
Published version available here: http://www.emeraldinsight.com/journals.htm?issn=1355-2554&volume=18&issue=6&articleid=17054913
Keywords: Enterprising behaviour; Perseverance; Goal strategies